The mathematics of Oz : Mental gymnastics from beyond the edge - Pickover, Clifford A. (Cambridge, U.K. : New York : Cambridge University Press, 2002)
"Grab a pencil. Relax. Then take off on a mind-boggling journey to the ultimate frontier of math, mind, and meaning as author Dr. Clifford Pickover, Dorothy, and Dr. Oz explore some of the oddest and quirkiest highways and byways of the numerically obsessed. Prepare yourself for a shattering odyssey as The Mathematics of Oz unlocks the doors of your imagination. The thought-provoking mysteries, puzzles, and problems
Includes bibliographical references (p. 347-348) and index.
Keywords: Mathematical recreations